FEATURES OF IMPROVING THE MEDICAL SERVICES PROVISION IN UKRAINE - Havrilyuk, A.A.; Zharlinska, R.G.; Datsenko, Н.V.; Sorokoumov, V.P.; Міщук, А.А.; Kotuza, A.S. (World of Medicine and Biology, 2019)
In the article, the authors identified the nature and features of healthcare services in the context of legal and marketing approach. The classification of healthcare services using economic and legal criteria is proposed. The assessment of medical services as an object of legal regulation in Ukraine at the present stage is given. Some aspects of functioning of the market of medical services, in particular their advertising, are studied. Proposals have been made to improve the current legislation governing the market for medical services in Ukraine, based on international legal standards.
Keywords: healthcare market; healthcare organization; competition; healthcare service; legal regulation